Implementation model of Digital Transformation projects in Boutique Hotels (2020)
Digital transformation has become an imperative of competitiveness for companies. However, there is a knowledge gap on the subject mainly in countries like Colombia and more in industry sectors where the use of information technologies has traditionally been low. In these sectors, although they recognize the advantages and needs of adopting digital transformation, it is not clear how and where to start. This research aims to provide knowledge to decision makers on how to adopt and initiate such transformation, select and validate an implementation model for digital transformation projects. The validation of the model was carried out in a set of boutique hotels in the city of Cartagena. © 2020 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.